Literature Review: The Effect of Folic Acid and Vitamin B6 Content in Dates on Ovulation Quality in Women of Childbearing Age - Sarmila Mustakim; Nasruddin Andi Mappaware; Suzanna J.M Siegers (PSPP JOURNALS, 2026)
Ovulation quality is a crucial component of reproductive health in women of childbearing age because it plays a role in successful fertilization and the sustainability of the reproductive process. Ovulation quality is influenced by oocyte maturation, follicle development, hormonal balance, and ovarian environmental conditions. Nutritional status, particularly adequate intake of folic acid and vitamin B6, is known to play a crucial role in supporting this process. Dates (Phoenix dactylifera L.) are a natural food source containing folic acid, vitamin B6, and bioactive compounds that have the potential to support ovarian function. This study aims to examine the effect of folic acid and vitamin B6 content in dates on ovulation quality in women of childbearing age. The method used was a literature review with a narrative design. Data were obtained from national and international journal articles relevant to the nutritional content of dates, the role of folic acid and vitamin B6, and their relationship to ovulation quality. Data were analyzed descriptively by grouping findings based on the biological mechanisms involved in ovulation. The study results indicate that folic acid plays a role in deoxyribonucleic acid synthesis and oocyte maturation through the one-carbon metabolic pathway, while vitamin B6 plays a role in regulating homocysteine ​​metabolism and ovarian metabolic balance. Furthermore, the bioactive compounds in dates have the potential to help suppress oxidative stress, which can damage oocyte quality. The conclusions of this study suggest that dates have the potential to support ovulation quality through complementary nutritional and biological mechanisms, although further clinical research is needed to strengthen the evidence directly.